2010
DOI: 10.1007/s10488-010-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of HIV and Psychotropic Medications among Persons with Serious Mental Illness and HIV/AIDS

Abstract: Persons with serious mental illness (SMI) have higher rates of co-morbid HIV disorders compared to the general population. There are concerns that the SMI/HIV population may be receiving fewer HIV and psychotropic medications due to problems of access and concerns by providers associated with following complex medication regimes. The purpose of this study was to examine any disparity in medication treatment of the SMI/HIV population by comparing medication use and continuity of prescription fills to groups tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Patients with a triple diagnosis are less likely to receive treatment for their mental illness or for their substance abuse disorder 23. In addition, the co-occurrence of the three diagnoses is associated with decreased receipt of highly active antiretroviral therapy (HAART) and viral suppression,24 and decreased adherence to treatment 25,26. Our results support these concerns.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Patients with a triple diagnosis are less likely to receive treatment for their mental illness or for their substance abuse disorder 23. In addition, the co-occurrence of the three diagnoses is associated with decreased receipt of highly active antiretroviral therapy (HAART) and viral suppression,24 and decreased adherence to treatment 25,26. Our results support these concerns.…”
Section: Discussionsupporting
confidence: 59%
“…Only 14 of the 25 (56%) HIV-infected patients received antiretroviral therapy, even though most of these patients had been identified as HIV-positive more than 6 months prior to the study and 12 patients had been HIV-positive for over 7 years. Therefore, it has been suggested that an integrative approach combining HIV, substance abuse, and mental health treatment might improve outcomes in this population 24,26. Unfortunately, the results from The HIV/AIDS Treatment Adherence, Health Outcomes and Cost Study, which evaluated the cost-effectiveness of integrated HIV primary care, mental health, and substance abuse services among triply diagnosed patients, have been somewhat disappointing 27.…”
Section: Discussionmentioning
confidence: 99%
“…For example, greater depressive symptoms are associated with poorer psychotropic and antiretroviral adherence, with greater adherence to psychotropics predicting better adherence to antiretrovirals (Cruess et al, 2012). Compared to persons with either HIV infection or psychiatric conditions, dually diagnosed individuals are less likely to fill prescriptions for psychotropics and antiretroviral (Lee, Rothbard, Noll, & Blank, 2011). Substance use is one factor that may influence adherence to both classes of medications (Chitsaz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of HIV infection among persons with serious mental illness (SMI) is estimated to be between 3% and 23%, or more than 10 fold higher than the 0.4% in the general United States population (Cournos and McKinnon, 1997; Lee et al, 2011; Meyer, 2003). Due to the high SMI prevalence in this population, psychotropic medications are commonly used by HIV-infected patients (Bing et al, 2001; Gaynes et al, 2008; Thompson et al, 2006; Vitiello et al, 2003; Walkup et al, 2004).…”
Section: Introductionmentioning
confidence: 99%